The Social & Mobile Learning Experiences of Students Using Mobile E-books - Kissinger, Jeff S (Online Learning, 2013)
This research was designed to explore the learning experiences of state college students using mobile e-book readers. The purpose of the study was to build a rich description of how students used electronic textbooks delivered on mobile computing devices for college-level, introductory sociology courses at a Southeastern public state college in the United States. This research employed a multiple case study design that thoroughly investigated and documented student experiences with this instructional technology. The bounding frame was comprised of the literature on mobile technology, mobile learning theories, and e-books. Situated within the mobile learning framework was a theoretical lens of learning theories commonly found in the literature on mobile learning (constructivism, social cognitive theory, self-efficacy theory, expectancy x value theory, self-determination theory, and situated cognition). This lens was used to provide insight into the student’s learning experiences. Students were found to be competent with the e-books, confident, metacognitive, and desirous of more social learning opportunities within their e-books. Six major conclusions were reached. These were: (1) students expressed competence in their use of the mobile e-books, (2) students expressed feelings of high self-efficacy when using the mobile e-books, (3) students overall valued the use of the e-book for their learning, (4) students were individualized and metacognitive in their learning with the mobile e-books, (5) students enhanced their learning socially and within situated learning opportunities, and (6) the students and the instructor had divergent views on the value and utility of social, interactive textbooks.